P017 Human intestinal pro-inflammatory CD11chigh macrophages, but not their transient CD11cdim or tolerogenic CD11c- counterparts, are expanded in inflammatory bowel disease. (16th January 2018) - Bernardo, D; Marín, A C; Fernández Tomé, S; Montalbán-Arqués, A; Carrasco, A; Tristán, E; Mora-Gutiérrez, I; Díaz-Guerra, A; Caminero-Fernández, R; Miranda, P; Casals, F; Caldas, M; et al.
Abstract: Background: Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is thought to be driven by an exacerbated immune response to the commensal microbiota. Macrophages (MΦ) are the most abundant mononuclear phagocytes in the gastrointestinal tract, where they are critical at shaping the type of immune elicited towards the microbiota. However, there is not much available information about human MΦ subset composition, phenotype and function in the gastrointestinal tract. Here, we aimed to characterise intestinal MΦ in health and in patients with inflammatory bowel disease (IBD) Methods: Colonic biopsies were obtained from the inflamed and non-inflamed tissue from IBD patients (CD and UC), as well as from the non-inflamed tissue from quiescent patients and healthy controls. Biopsies were immediately processed and lamina propria mononuclear cells characterised by flow cytometry both in resting conditions and after overnight culture in the presence/absence of a pattern recognition receptor agonist (LPS). Colonic biopsies were also directly cultured to obtain cell-free culture supernatants, which were used both to condition GM-CSF-derived MΦ and to assess mucosal recruitment capacity of CD14 + monocytes Results: Human intestinal MΦ were identified within singlet viable cells as CD45+HLA-DR+CD14+CD64+ and further divided into a waterfall of CD11c high, CD11c dim and CD11c- subsets. While CD11c high cells displayed a monocyte-like phenotype, the CD11c dim subset shown an intermediate phenotype towards CD11c- MΦ-like cells, which had higher levels of HLA-DR and CD64 coupled with lower expression of CX3CR1, SIRPα, CCR2 and CD40. CD11c high MΦ cells produced IL-1β, both in resting conditions and after LPS stimulation, compared with the CD11c- MΦ subset which produced IL-10. CD11c high MΦ cells, but not the other subsets, were expanded in the inflamed colon from IBD patients (both UC and CD) but not on the non-inflamed mucosa. Tolerogenic IL-10 producing CD11c- MΦ were generated from CD14 + monocytes following mucosal conditioning. Finally, the colonic mucosa recruited circulating CD14 + monocytes in a CCR2-deppendent manner, being such capacity expanded in IBD. Conclusions: MΦ subsets represent transition stages from newly arrived pro-inflammatory monocytes (CD11c high ) into transient (CD11c dim ) and resident (CD11c-) MΦ as reflected by the mucosal capacity to recruit circulating CD14 + monocytes and induce CD11c- MΦ. However, this process is dysregulated in IBD, where there is an increased migration and accumulation of CD11c high cells.